Predictors of Weight Loss and Weight Loss Maintenance in Children and Adolescents With Obesity After Behavioral Weight Loss Intervention - Weiland, Alisa; Nannette, Lena Kasemann; Zipfel, Stephan; Ehehalt, Stefan; Ziser, Katrin; Junne, Florian; Mack, Isabelle (Frontiers in Public Health, 2022)
Objective: Predictors of body weight loss (BWL) and body weight loss maintenance (BWLM) after behavioural weight loss intervention are well investigated in adults. Less is known for children and adolescents and a systematic overview on the topic for this age group was aim of the review. Methods: A systematic research according to PRISMA guidelines using several databases was performed. The outcome was the BMI z-Score of longitudinal studies. The extracted predictors were classified in clusters (Physiology, Behaviour, Psychology, Environment) and compared with a theory-driven model based on international guidelines and known predictors for adults. Results: Out of 2623 articles 24 met the eligibility criteria, 23 investigating BWL and 8 BWLM. The expected key predictor in research for adults “Behaviour” was hardly investigated in children. The most examined cluster was “Physiology” with the most significant predictors, in particular genetics (BWL) and blood parameters (BWLM). Factors in the cluster “Psychology” also predicted BWL and BWLM. The cluster “Environment”, which was highlighted in most intervention guidelines, was neglected in studies regarding BWLM and hardly investigated in studies with BWL. Conclusions: The comparison with the theory-driven children model outlined research gaps and differences between predictors for adults and children providing further direction of research.